2015
DOI: 10.1186/s13395-015-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro stability of therapeutically relevant, internally truncated dystrophins

Abstract: BackgroundThe X-linked recessive disease Duchenne muscular dystrophy (DMD) is caused by mutations in the gene encoding the protein dystrophin. Despite its large size, dystrophin is a highly stable protein, demonstrating cooperative unfolding during thermal denaturation as monitored by circular dichroism spectroscopy. In contrast, internal sequence deletions have been associated with a loss of the cooperative unfolding and cause in vitro protein aggregation. Several emerging therapy options for DMD utilize inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…Use of hinge 2 has the advantage of maintaining the natural linkage to the R1–3 domain, whereas use of hinge 3 would create a novel junction. Novel juxtapositions of protein domains may promote immune responses 59 or result in protein misfolding, which in turn may either promote degradation 60 , 61 or result in formation of protein inclusions. 34 , 62 …”
Section: Discussionmentioning
confidence: 99%
“…Use of hinge 2 has the advantage of maintaining the natural linkage to the R1–3 domain, whereas use of hinge 3 would create a novel junction. Novel juxtapositions of protein domains may promote immune responses 59 or result in protein misfolding, which in turn may either promote degradation 60 , 61 or result in formation of protein inclusions. 34 , 62 …”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 The juxtaposition of different SRs and hinges that are not adjacent to one another in the full-length protein also affect the tertiary structure, stability, and solubility of μDys. 19 , 42 , 49 , 50 Nonetheless, the carboxy-terminal and most of the SR domains can be removed from dystrophin with only modest reductions of striated muscle performance. 15 , 19 The variable degrees of effectiveness of μDys tested to date suggested that versions with improved function might be designed.…”
Section: Introductionmentioning
confidence: 99%
“…There is thus still a need for a fully quantitative and standardized method to accurately quantify dystrophin over a wide range of levels, preferably making use of a representative reference control to allow comparison between clinical studies in pre-treatment versus post-treatment samples. Full-length purified dystrophin protein that can serve as a reference standard is not currently available due to the large size and low expression of the dystrophin protein [ 22 ].…”
Section: Introductionmentioning
confidence: 99%